Performance characteristics of some eastern and southern African Zebu cattle breeds - Tawah, C.L.; Rege, J.E.O. (South African Society of Animal Science, 1996)
The zebu cattle "breeds" of eastern and southern Africa are broadly classified into "large" and "small" types. Boran, Karamajong and Sudanese Zebu are examples of the former, while those of the latter include Angoni, Nkedi and Nandi. The habitat of the large zebu is drier than that of the small types. Growth, fertility, survival, carcass and milk produciton are the traits reviewed. Most of these traits show evidence of tremendous variability which may be due partly to differences in the production systems and agro-ecological zones and partly to the genotype. As expected, improved standards of management and reduced disease risk contribute to the remarkable performance characteristics of some breeds, notably the Boran and Angoni. The small zebus are more fertile than the large types, as expected.They are, thus, better apt for low-input production systems than the latter. Under improved nutrition, both breed types demonstrate high aptitudes to gain weight and to aproduce reasonable carcasses. On the other hand, the "large" types (e.g. Western Baggara and Boran) have evolved adaptive mechanisms to enable them overcome the long periods of feed scarcity as reflected in their great capacity to rapidly build-up body reserves during periods of pasture abundance. They also show characteristic ability for high rate of compensatory growth which enables them to achieve rapid and exceptional gains when fattened. The "unimproved" Orma Borann show greater ability to resist trypanosomiasis than "improved" Boran in Kenya. Although they produce both meat and milk, Butana and Kenana manifest greater dairy aptitudes, while Western Baggara and Boran show greater beef potentials. Selective breeding is, Thus, expected to enhance their meat and dairy potentials under moderate to high standards of feeding, management and disease control. Further studies are deemed necessary to fully characterise the biological performance and adaptation of these breeds in their natural environments.